Eccentric exercise induces spatial changes in the mechanomyographic activity of the upper trapezius muscle. (8th March 2018) - Madeleine, P.; Hansen, E. A.; Andersen, R. E.; Kumorek, M.; Mroczek, D.; Samani, A.; Kawczyński, A.
Abstract : In this study, we hypothesized that the recordings of multichannel mechanomyography (MMG) of the upper trapezius muscle would reveal spatially dependent manifestations in the presence of delayed onset muscle soreness occurring 24 hours after eccentric exercise (ECC). Sixteen participants performed high‐intensity eccentric exercises (5 sets of 10 eccentric contractions at 100% of max elevation force) targeting the upper trapezius on their dominant side. Twelve accelerometers were attached to record MMG activity during submaximal exercise consisting of static and dynamic arm flexion and abduction. Measurements were taken before and 24 hours after ECC. Average rectified value (ARV), percentage of determinism (% DET), and recurrence (% REC) of the MMG signals were computed to estimate the level of muscular activity and the magnitude of regularity of the MMG. The ARV, % REC, and % DET maps revealed heterogeneous MMG activity of the upper trapezius 24 hours after ECC when compared with before. Increased ARV, % REC, and % DET were found 24 hours after ECC when compared with before. The study provides new key information on how a single muscle responds to ECC. Our findings suggest that multichannel MMG and nonlinear analyses may detect muscular and musculo‐tendinous alterations due to ECC.